2015
DOI: 10.3390/agriculture5041116
|View full text |Cite
|
Sign up to set email alerts
|

Carbon Assimilation, Biomass Partitioning and Productivity in Grasses

Abstract: Plant growth correlates with net carbon gain on a whole plant basis. Over the last several decades, the driving factors shaping plant morphology and performance have become increasingly clear. This review seeks to explore the importance of these factors for grass performance. Briefly, these fall into factors influencing photosynthetic rates directly, competition between plants in a canopy, and nutrient status and availability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
53
0
8

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(71 citation statements)
references
References 102 publications
(118 reference statements)
1
53
0
8
Order By: Relevance
“…The typical regrowth interval in dairy grazing systems is between 20 and 60 days, varying depending on temperature, radiation intensity, and water and nutrient availability. The critical ecophysiological processes supporting the accumulation of mass have been well documented in the research reviewed in this special issue [1,10,11]. They include: the emergence and expansion of new leaves from the tiller apical meristem to replace lamina area and increase light interception and carbon (C) assimilation; the mobilisation of some stored C and nitrogen (N) to support new leaf production and Rubisco synthesis, with subsequent replenishment of those stores once the energy and N status of the whole plant recovers; changes in the relative allocation of available C between the shoot and root systems, initially to promote new leaf growth, and subsequently to resume root growth so that the capacity to assimilate nutrients and water remains in balance with the increase in C assimilation capacity of the canopy; tiller initiation and emergence and consequent effects on sward tiller density; changes in leaf morphology including the specific and absolute area of the new leaves produced as the plant responds to its changing energy status; and the turnover of older leaf material entering senescence including re-translocation of some constituents of old leaves, especially N, to support new growth.…”
Section: Critical Ecophysiological Principles and Their Translation Tmentioning
confidence: 97%
See 1 more Smart Citation
“…The typical regrowth interval in dairy grazing systems is between 20 and 60 days, varying depending on temperature, radiation intensity, and water and nutrient availability. The critical ecophysiological processes supporting the accumulation of mass have been well documented in the research reviewed in this special issue [1,10,11]. They include: the emergence and expansion of new leaves from the tiller apical meristem to replace lamina area and increase light interception and carbon (C) assimilation; the mobilisation of some stored C and nitrogen (N) to support new leaf production and Rubisco synthesis, with subsequent replenishment of those stores once the energy and N status of the whole plant recovers; changes in the relative allocation of available C between the shoot and root systems, initially to promote new leaf growth, and subsequently to resume root growth so that the capacity to assimilate nutrients and water remains in balance with the increase in C assimilation capacity of the canopy; tiller initiation and emergence and consequent effects on sward tiller density; changes in leaf morphology including the specific and absolute area of the new leaves produced as the plant responds to its changing energy status; and the turnover of older leaf material entering senescence including re-translocation of some constituents of old leaves, especially N, to support new growth.…”
Section: Critical Ecophysiological Principles and Their Translation Tmentioning
confidence: 97%
“…They showed that when pasture is defoliated to a very low residual LAI, the initial rate of regrowth is retarded since the first leaf produced post-defoliation is restricted in size due to the limited amount of energy available to invest in the lamina of that leaf. Since leaf emergence rate and leaf elongation duration are relatively insensitive to defoliation severity within the range normally applied in farming systems [10], the plant is unable to compensate for the loss of C assimilation capacity (despite the mobilisation of carbohydrate reserves plus changes in specific leaf area [11]) and the first leaf is necessarily restricted in size. Subsequent leaves are larger as C assimilation capacity increases and the full extent of compensatory effects (such as cessation of C export to roots to support new leaf growth [29]) is realised.…”
Section: The Ecophysiological Basis Of Current Grazing Management Recmentioning
confidence: 99%
“…Discussion then turns to leaf area index, light capture, and assimilate allocation within the plant. Despite studies establishing that the red:far-red light ratio at the tiller base operates as a switching mechanism for tiller initiation, as well as the existence of a -4/3 allometric relationship between mean shoot dry mass and mean shoot density, knowledge of interactions between shoots, of the extent and circumstances of sharing or competition for N and C, and of the principles that determine allocation to various categories of root remains rudimentary [36].…”
Section: Plant Physical and Physiological Systemsmentioning
confidence: 99%
“…Two contributions to this volume provide reviews at this level [36,37]. Irving [36] notes that grasses provide roughly 50% of human energy consumption globally, either directly or indirectly as forage for meat production. Carbon fixation is seen as a prime driver of plant growth.…”
Section: Plant Physical and Physiological Systemsmentioning
confidence: 99%
“…Resultados semelhantes aos do presente estudo foram encontrados por Paula et al (2012) Em gramíneas o colmo é um componente importante na sustentação da planta (FAGUNDES et al, 2006). Além disso, a proporção do material fotossintetizado que é alocado para os colmos aumenta quanto mais a planta cresce (IRVING, 2015). Dessa forma, maior proporção de colmos nos dosséis mais altos já era esperado.…”
Section: Discussionunclassified